1999
DOI: 10.1111/j.1349-7006.1999.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MDM2 in MCF‐7 Promotes Both Growth Advantage and p53 Accumulation in Response to Estradiol

Abstract: The overexpression of the oncogene product MDM2 is often observed in human breast cancer cells, especially in estrogen receptor (ER)-positive ones. To study the role of MDM2 protein in ERpositive breast cancer, we have established cell lines derived from MCF-7 which stably express increased and decreased levels of MDM2 by transfection of a mammalian expression vector containing human mdm2 cDNA in sense and antisense orientations, respectively. Interestingly, MDM2 overexpression in MCF-7 cells afforded a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…T47D human breast cancer cells, containing a mutant form of p53, restored elevated p53 levels following treatment with estradiol (17). In addition, wild-typep53 MCF7 breast cancer cell lines overexpressing Mdm2 demonstrated increased steady-state levels of p53 in the presence of estradiol (45). Studies using murine models assessing estrogen stimulation of the mammary gland not only reported increased levels of nuclear, functional p53 (21, 49) but also demonstrated that hormone stimulation is necessary for a maximal p53-mediated response to ionizing radiation (1).…”
Section: Discussionmentioning
confidence: 90%
“…T47D human breast cancer cells, containing a mutant form of p53, restored elevated p53 levels following treatment with estradiol (17). In addition, wild-typep53 MCF7 breast cancer cell lines overexpressing Mdm2 demonstrated increased steady-state levels of p53 in the presence of estradiol (45). Studies using murine models assessing estrogen stimulation of the mammary gland not only reported increased levels of nuclear, functional p53 (21, 49) but also demonstrated that hormone stimulation is necessary for a maximal p53-mediated response to ionizing radiation (1).…”
Section: Discussionmentioning
confidence: 90%
“…For experiments evaluating the effect of E2, cells were cultured in phenol red-free RPMI1640 (PRF-RPMI, Gibco BRL) containing 10% FBS stripped of steroids by absorption to dextran-coated charcoal (DCC-FBS). MCF-7/pCmdm2 clones S1 and S3 were established by transfection of mammalian expression vector containing human mdm2 cDNA (pCmdm2) into MCF-7 cells as described previously (29,30). Saos-2, a p53-deficient osteosarcoma cell line, was from American type culture collection (Manassas, VA) and grown in McCoy's 5A medium (Gibco BRL) containing 15% FBS and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of such protection in BALB/c p53-null mammary epithelium further strengthened the pivotal role of p53 in hormone-induced protection against carcinogenesis (25). In MDM2-overexpressing breast cancer cells, enhanced ERa function was observed and E2 stabilized wild-type p53 without any increase in p53 gene transcription (26,27). Further, p53 has been reported to be in a ternary complex with ERa and MDM2 (28).…”
Section: Introductionmentioning
confidence: 93%